Repotenciación del sistema de control y distribución de cargas eléctricas para las bombas de vacío de la hacienda “El Futuro S.A.” - Tipan Caisa, Luis Wilmer (2023)
The Hacienda "El Futuro S.A." Before the implementation of the technological proposal, the electrical systems were poorly designed, as was the distribution of electrical charges, leaving the electromechanical equipment disabled, the same ones that were caused by an inadequate electrical installation in the distribution board, which had a negative influence. in the power factor and the existence of a bad dimensioning of the electrical equipment, for which the opportunity arose to repower the electrical control panel and the distribution of electrical charges to the milking equipment, through the implementation of a bank of capacitors to correct the power factor and implement the grounding system to protect the milking equipment from electrical discharges in the Hacienda "El Futuro S.A.", said investigation corresponds to the modality of technological proposal, which was carried out using methods of inductive, scientific and experimental research, which allowed obtaining the necessary strategies for the development of the redesign of the electrical systems to be installed, obtaining as results the AWG conductor of caliber No. 2, motor protectors of (20 - 25) A, capacitor bank of 6.66 kVAR, and grounding system with a resistance of 5 ohms to avoid loss of sensitive electronic equipment. Through the installation of electrical equipment, it was possible to correct the power factor that previously was 0.87 to 0.94 and it was possible to obtain a decrease in voltage drops for the operation of all electrical equipment, creating continuous production in the milking